2019
DOI: 10.1042/bsr20182271
|View full text |Cite
|
Sign up to set email alerts
|

A modified SDS-based DNA extraction method from raw soybean

Abstract: Soybean is the most important genetically modified (GM) oilseed worldwide. Regulations relating to the approval of biotech soybean varieties and product labeling demand accurate and reliable detection techniques to screen for GM soya. High-quality extracted DNA is essential for DNA-based monitoring methods. Thus, four widely used protocols (SDS, CTAB, DP305, and DNeasy Plant Mini Kit) were compared in the present study to explore the most efficient DNA extraction method for raw soya matrix. The SDS-based metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…It is suggested that SDS-based DNA extractions could be more appropriate for oily plant matrices like ground poppy seeds. The SDS-containing method modified for ground raw soybean seeds had the highest yield of DNA in comparison with the CTAB method and two commercial kits [ 39 ]. A lower amount of DNA yielded the CTAB method also from soybean flour [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that SDS-based DNA extractions could be more appropriate for oily plant matrices like ground poppy seeds. The SDS-containing method modified for ground raw soybean seeds had the highest yield of DNA in comparison with the CTAB method and two commercial kits [ 39 ]. A lower amount of DNA yielded the CTAB method also from soybean flour [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bal31 Sensitivity Assay HMW genomic DNA was extracted from 50 Anopheles albimanus following an SDS-based method as previously described [36]. The Bal31 Sensitivity Assay was performed based on the protocol of [20,21] with several modifications.…”
Section: Repeat Analysismentioning
confidence: 99%
“…However, commercial kits are usually expensive, with reagent costs commonly ranging between 2 and 9 US$ per sample [8,28], and many times provide low yields, insufficient for some NGS applications [8,29].…”
Section: Introductionmentioning
confidence: 99%